The Phenomenon of Changes in Student Behavior During Large-Scale Social Restrictions - Nurfuadi Nurfuadi; Nurkholis Nurkholis; Amanda Retno Putri (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The impact of Large-Scale Social Restrictions in Indonesia currently has a major impact on behavioral changes that occur as a result of the Covid-19 pandemic. This study aims to analyze the phenomenon of changes in student behavior during Large-Scale Social Restrictions (PSBB) in the RA Kartini Cluster. The method used in this research is a qualitative method with the type of case study research. With the research subject, 7 teachers and 6 students in grades I-VI in the RA Kartini Cluster. The results of this study indicate that the impact of Large-Scale Social Restrictions that occurred in the RA Kartini Cluster was a change in student behavior such as changes in Discipline, Honesty, Social Care, Communication and Religious behavior. Based on the findings of this study, it can be concluded that the impact of Large-Scale Social Restrictions on student behavior occurs because of learning policies that make students feel less interested in learning as a result of various behavioral changes in the RA Kartini Cluster.